Corporate social responsibility reporting and corporate reputation : an institutional and resource-based perspective / Suaini Othman - Othman, Suaini (2012)
Prompted by calls for greater accountability and transparency and in line with the prevailing Corporate Social Responsibility (CSR) reporting practices at the international level, the Malaysian regulatory authorities have made it mandatory for all public-listed companies to disclose their CSR activities in their annual reports beginning with the financial year ending 31 December 2007. The government believes that CSR reporting can be a potent tool for Malaysian companies to realise their enhanced reputation and in turn will assist them to compete effectively in the global market. Therefore, the objective of this study is to examine factors that influenced managements' decisions on the quantity and quality of CSR disclosure during the unregulated (2005 and 2006) to the regulated (2007 and 2008) periods and whether these disclosures will have any effect on corporate reputation. The moderating and mediating effects in relation to CSR disclosures are also examined. Institutional Theory and Resource-based Perspective have been integrated to underpin this study. This study embarked upon a sequential mixed method approach, a combination of qualitative and quantitative investigations. The qualitative investigation involved faceto-face interviews with CSR managers while the quantitative investigation was based on content analysis of the annual reports of 248 companies listed on the main board of Bursa Malaysia over a period of four years, involving a total of 992 firm-year observations. The quantity of CSR disclosure was measured using word counts while the quality disclosure was measured based on an index comprised of 100 indicators, using international and national CSR values as yardsticks. An objective measure for corporate reputation based on dimensions of the RepTrak ™ model modified according to suggestions made by a panel of experts was also constructed. The findings provide evidence that the quality of CSR disclosures enhances corporate reputation. The results of both the quantity and quality measures indicate strong evidence that government regulation is an effective mechanism in enhancing CSR disclosure. While the government-owned companies expressed strong support for the regulator's call for more accountability and transparency in relation to their CSR disclosures, the family-owned companies were less inclined to disclose information beyond the basic regulatory requirements. Nevertheless, the results demonstrate that the presence of superior leadership can moderate the resistance to change by these family-owned companies towards CSR reporting. The competencies of these superior leaders are shown to be central in driving excellence of CSR disclosures in Malaysia. In situations of uncertainty, companies in the concentrated industry tend to emulate the CSR disclosure practices of companies that advocated quality reporting as their benchmark. Finally, the mediation tests affirm that both the quantity and quality of CSR disclosures can function as information signals to enhance corporate reputation. Overall, these results suggest that CSR disclosures are important tools for corporate reputation enhancement. These findings provide valuable insights to the regulators, practitioners and academicians in enhancing corporate accountability and transparency. The results are also expected to address concerns often expressed by sceptics about the tangible benefits of CSR disclosure, thus underscoring the importance of CSR reporting.